INTEGRASI ANGGOTA TIM KERJA SMK TERAKREDITASI A DAN C DALAM MEMENUHI STANDAR NASIONAL PENDIDIKAN - Ika Indriasari; David Firna Setiawan; Aryan Eka Prastya Nugraha (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Competition in gaining public trust is an important factor that must be considered by all available resources in each vocational school. The statement is based on the 2015 Central Bureau of Statistics data which shows that the number of Vocational Schools throughout Indonesia has shown 12,421. This study aims to collect data on information among members of the Vocational Team in meeting national education standards. Furthermore, the data is used to analyze the integration process of work team members in accredited C and vocational high school vocational high school A. The approach used in this study is an inductive approach where the results of research are generalized to more general events. The results of the analysis obtained the results of Sig. (2-tailed) A1 of 0.004 <0.05, A2 of 0.003 <0.05 and A3 of 0.001 <0.05, so according to the decision making in the independent t-test, there were differences between Integration of members of the Vocational Work Team is accredited A and accredited C. Based on the results of data processing, it can be concluded that the integration process of the work team members in C-accredited Vocational Schools is not maximal. Keywords: Accreditation, Member Integration, National Education Standards